Creation of words as way of presenting of children`s world (on materials of work A.A. Usachev) (Eurasian Journal of Philology Science and Education, 2016)
In article considered questions about researching of poetic texts, transmission feature notional and stylistic organization of children`s speeches. A.A. Usachev shows on his material works, specific children perception of the world and their representation of language. At the same time important role perform individual-author`s neoplasms (occasional), in the majority, creation by commonly used model words. A.A. Usachev used on his work neoplasms not just for imitation children`s speech, in this case they can plug children`s traditional speech. Occasional invite children`s attention and to force him to pay attention meaning of the word. Frequently, new words create to named non-existent reality, on poetical texts of A.A. Usachev`s they create humorous effect. Exploration individual word creation – problem of the modern linguistics. Author`s neoplasms present illustration path and form to develop language, their study helps to identify trends to the word-formation processes, a the same time authors neoplasms give an idea about the features of the artist idiostyle word.
Keywords: children`s speech; children’s literature; word creation; occasional; rederivation; language game.